SIKAP KEBERAGAMAN DALAM TRADISI AGAMA-AGAMA IBRAHIM - Sumbulah, Umi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2007)
Researchs on Abrahamic religions found three religious attitudes which generate the theory of exclusivism, inclusivism and pluralism. Those sort of religious attitudes are constructed by normative doctrines and historical experience of each religion’s adherents in interacting with adherents of other religions. Pluralism as a philosophycal system of thinking emerges as a response toward inappropriateness of monism and dualism theories. Besides, socio-theological response also emerges as various thruth phenomena. Therefore, the phenomena should be responded wisely.